Pengaruh Kompetensi, Beban Kerja dan Motivasi terhadap Kinerja Pegawai melalui Insentif sebagai Variabel Intervening pada Pengelola Keuangan di Sekolah Dasar Negeri Tanjung Pinang - Lisah, Lisah; Indrayani, Indrayani; Indrawan, Mohamad Gita (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of competency, workload and motivation variables on employee performance through incentives for financial managers at SDN Tanjung Pinang. Data analysis using SEM-PLS (structural Equation Modeling-Partial Least Square). The results of this study found that competence has a positive but not significant effect on employee performance, workload has a negative and significant effect on employee performance, motivation has a positive and significant effect on employee performance, competence has a positive but not significant effect on wages, workload has a positive and significant effect on incentives, motivation has a positive and significant effect on incentives, incentives have a positive and significant effect on performance, competence has a positive and significant effect on performance with incentives as an intervening variable, workload has a positive and significant effect on performance with incentives as an intervening variable, motivation has a positive and significant effect on performance with incentives as an intervening variable.